2022
DOI: 10.1177/23259671221088009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sports-Related Traumatic Hip Dislocations Reported in United States Emergency Departments, 2010-2019

Abstract: Background: Traumatic hip dislocations are rare injuries that most commonly occur in motor vehicle accidents. There is a paucity of literature that describes sports-related hip dislocations. Purpose: To estimate the incidence of sports-related hip dislocations and determine any sport- or sex-related epidemiological trends using the National Electronic Injury Surveillance System (NEISS) database. Study Design: Descriptive epidemiology study. Methods: Data regarding sports-related hip dislocations from 2010 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4,8,18,25,31 The National Electronic Injury Surveillance System (NEISS) is a publicly accessible database from the United States (US) Consumer Product Safety Commission that has been used to analyze trends in sports-related orthopaedic injuries presenting to emergency departments (EDs) in the US. 16,20,21,26,27,32 NEISS data are gathered from a representative sample of 100 hospitals selected from the over 5000 US EDs with a minimum of 6 beds and 24-hour services. Currently, only 3 studies exist in the literature that analyze surfing-related injuries utilizing the NEISS.…”
mentioning
confidence: 99%
“…4,8,18,25,31 The National Electronic Injury Surveillance System (NEISS) is a publicly accessible database from the United States (US) Consumer Product Safety Commission that has been used to analyze trends in sports-related orthopaedic injuries presenting to emergency departments (EDs) in the US. 16,20,21,26,27,32 NEISS data are gathered from a representative sample of 100 hospitals selected from the over 5000 US EDs with a minimum of 6 beds and 24-hour services. Currently, only 3 studies exist in the literature that analyze surfing-related injuries utilizing the NEISS.…”
mentioning
confidence: 99%
“…These findings help to raise clinical awareness of these injuries because osteonecrosis may have few treatment choices for young athletes. 5,6 Since the labrum and acetabulum are deep, the joint capsule is robust, and there are strong muscular structural supports, this is a genuine ball and socket joint that is unlikely to dislocate. For the hip joint to separate, Arvidsson showed that a traction force of 400 N (90 lbs) was necessary.…”
mentioning
confidence: 99%